The influence of circulating anti-Müllerian hormone on ovarian responsiveness to ovulation induction with gonadotrophins in women with polycystic ovarian syndrome: a pilot study - Amer, Saad A.; Mahran, Ahmad; Abdelmaged, Ayman; El-Adawy, Ahmad R.; Eissa, Moustafa K.; Shaw, Robert W. (BioMed Central, 2013)
Background Women with polycystic ovarian syndrome (PCOS) are known to have elevated circulating Anti-Müllerian hormone (AMH), which has been found to desensitize ovarian follicles to follicle stimulating hormone (FSH). The purpose of this study was to investigate the impact of high circulating AMH on ovarian responsiveness to ovulation induction with gonadotrophins in PCOS women.